2023
DOI: 10.1039/d2ey00062h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of charge selective contacts on the quasi Fermi level splitting of CuGa3Se5 thin film photocathodes for hydrogen evolution and methylviologen reduction

Abstract: The defect-copper chalcopyrite CuGa3Se5 is a promising photocathode material for solar hydrogen generation. Here we assess its performance with photoelectrochemical measurements and vibrating Kelvin probe surface photovoltage spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…The measurement configuration is shown in Figure S10. We previously showed that the SPV signal generated under these conditions equals the photovoltage V ph of the illuminated FTO/BiVO 4 electrode, 34,35 i.e., the difference of the electrochemical potentials at the front (E F,f ) and back (E F,b ). SPV spectra for a BiVO 4 photoelectrode in contact with the triiodide/iodide electrolyte are depicted in Figure 6a.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…The measurement configuration is shown in Figure S10. We previously showed that the SPV signal generated under these conditions equals the photovoltage V ph of the illuminated FTO/BiVO 4 electrode, 34,35 i.e., the difference of the electrochemical potentials at the front (E F,f ) and back (E F,b ). SPV spectra for a BiVO 4 photoelectrode in contact with the triiodide/iodide electrolyte are depicted in Figure 6a.…”
Section: ■ Results and Discussionmentioning
confidence: 97%
“…The advantage of SPS compared to conventional photoelectrochemical characterization techniques is the high sensitivity of the method, since already small charge carrier concentrations (10 10 per cm −2 ) result in potentials on the mV scale [85] . Recently, we have expanded VKP‐SPS to include solid‐liquid interfaces [86] . This is possible by covering the sample with a drop of the electrolyte and a glass cover slip, as shown in Figure 6A.…”
Section: Resultsmentioning
confidence: 99%
“…These experiments were conducted using the contact potential difference (CPD) method in air to initially eliminate the complexity of the solid/liquid interface and to independently compare results to the PEC characteristics. Such measurements have been used extensively for probing buried photovoltaic junctions, as well as for determining the quasi-Fermi level splitting in semiconductor photoelectrode materials. , As shown in Figure , for the case of InP/TiO x heterostructures, remarkable differences between the shapes and magnitudes of intensity-dependent SPV from TTIP/H 2 O and TDMAT/H 2 O samples are observed. In particular, the TDMAT/H 2 O sample exhibits an S-like dependence of SPV as a function of light intensity, with the onset of photovoltage only occurring at higher light intensities.…”
Section: Resultsmentioning
confidence: 99%